Les pratiques professionnelles des pomiculteurs exposés aux pesticides : des savoir-faire de métier aux pratiques stratégiques - Caroline Jolly; Alain Garrigou; Elise Ledoux (Perspectives Interdisciplinaires sur le Travail et la Santé)
In very small apple orchards, most pesticide preparation and spraying is the responsibility of the owner. Compliance with the prescribed preventive measures does not eliminate exposure, which can lead to health effects. The purpose is to describe the professional practices developed by apple growers. They aim to limit exposure to pesticides while producing quality fruit, thus contributing to the growth of their business. The intervention research, based on ecotoxicology approach, was carried out with apple growers in Quebec. The diversity of professional practices presented falls within the activity domains of strategic management (e.g. business development) and production management (e.g. spray application). These practices are influenced by external forces, resulting in trade-offs. They are complementary to current prevention measures and could be mobilized to better support the prevention of pesticide exposure in very small agricultural enterprises.